2007
DOI: 10.1002/chin.200704096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Self‐Assembling and Redox Properties of 2‐[(ω‐Sulfanylalkyl)amino]‐1,4‐naphthoquinones.

Abstract: Sulfur compounds Q 0980 Synthesis, Self-Assembling and Redox Properties of 2-[(ω-Sulfanylalkyl)amino]-1,4-naphthoquinones. -(KAZEMEKAITE, M.; RAILAITE, V.; BULOVAS, A.; TALAIKYTE, Z.; NIAURA, G.; RAZUMAS, V.; BUTKUS*, E.; Collect. Czech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The electron transfer depending on the distance has been also studied by using SAMs bound to redox moieties such as hydroquinone [15], naphthoquinone (NQ) [2][3][4] and azobenzene [16]. In the SAMs including quinone derivatives, proton transfer is essentially involved in the electron transfer process in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The electron transfer depending on the distance has been also studied by using SAMs bound to redox moieties such as hydroquinone [15], naphthoquinone (NQ) [2][3][4] and azobenzene [16]. In the SAMs including quinone derivatives, proton transfer is essentially involved in the electron transfer process in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transfer for SAM of various compounds with redox moieties on a gold electrode has been studied so that the rate constant is found to increase with decreasing the distance between the redox group and the electrode according to the Marcus theory [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The redox activity of physiological molecules like ubiquinone-10 (UQ 10 ) or plastoquinone-9 (PQ 9 ), solubilized in hydroxylic solutions, has been examined (Okamura and Feher, 1992). Various self-assembly methods were used to incorporate ubiquinones or plastoquinones at the interface between water and modified electrodes, either by means of direct adsorption at the electrode surface (Gordillo and Schiffrin, 1994) or by incorporation into alkanethiol monolayer (Takehara et al, 1991) it has been shown that newly synthesized 1,4-naphthoquinones linked via nitrogen atom through the short chain to the terminal sulfanyl group form self-assembled monolayers on gold electrode (Kažemėkaitė et al, 2006). Numerous model membrane systems have been developed for the studying the physicochemical behavior of quinone molecules inside a bilayer (Gennis, 1989).…”
Section: Redox Conversion Of Lipophilic Nqdmentioning
confidence: 99%